Equilibrium Study on Reactive Extraction of Lactic Acid with Tri-n – Butyl Phosphate in n - Hexane - Panut Mulyono; Anita Pardah (Department of Chemical Engineering, Universitas Gadjah Mada, 2013)
Extraction of carboxylic acids from dilute aqueous solution using traditional solvents such as ketones, alcohols, ethers, and ester is inefficient because the distribution ratio is rather low. Reactive extraction which exploits reversible chemical complexation is an effective separation process for extraction of carboxylic acids from aqueous streams such as fermentation broths and wastewaters. In the extraction process, selection of the solvent is an important aspect to be considered. Considering its solubility in water, cost and availability, tri-n-butyl phosphate (TBP) seems to be an attractive solvent for the extraction of lactic acid from aqueous solution. The purpose of this experiment is to study the equilibrium of the reactive extraction of lactic acid in aqueous solution with TBP in n-hexane. The parameters studied in this experiment were initial concentration of lactic acid in the aqueous phase, TBP concentration in n-hexane phase, and the extraction temperature. The experiments at ambient temperature were carried out using a separatory funnel, while the experiments at other than ambient temperature were carried out using erlenmeyer flask and water bath shaker to adjust the temperature. In this experiment, the initial concentration of lactic acid was varied from 0.1 to 0.5 gmol/dm3. The range of initial TBP concentrations in n-hexane was 0.1 to 1.0 gmol/dm3 and the extraction temperature range was 283 to 313 K. The experimental results showed that the higher the initial concentration of lactic acid in aqueous solution, the higher the distribution ratio for a fixed TBP concentration and extraction temperature. For a fixed initial concentration of lactic acid in aqueous solution and extraction temperature, the distribution ratio of lactic acid is increased by increasing TBP concentration. The overall equilibrium constants (Kpq) for the experiments using TBP concentration ranging from 0.1 to 1.0 gmol/dm3 at the extraction temperature of 293 K are calculated to be 0.0668 to 0.5144. Kpq for the experiments at the temperature ranging from 283 to 313 K at the initial concentration of lactic acid of 0.2 gmol/L are found to be 0.0122 to 0.8856. The Kpq as a function of temperature (T) in K can be expressed as ln Kpq = 10,596/T - 38.08 with sum of square of error of 0.14.